Perversion of justice the Jeffrey Epstein story - Brown, Julie K., 1961- (New York, NY Dey St., an imprint of William Morrow, 2021)
"Dauntless journalist Julie K. Brown recounts her uncompromising and risky investigation of Jeffrey Epstein's underage sex trafficking operation, and the explosive reporting for the Miami Herald that finally brought him to justice while exposing the powerful people and broken system that protected him"--
Introduction -- Joe -- Finding Jane Doe -- The police probe -- Eppy -- The Miami Herald -- Dead ends -- The first deal -- Music City -- Blood money -- Mike -- Follow the money -- Forever changed -- Operation Leap Year -- The sweetheart deal -- Dancing with wolves -- Courtney -- Virginia -- Finding Mr. Epstein -- Mar-a-Lago -- Madam Ghislaine -- The prince and the piper -- Starr power -- Bait and switch -- The get out of jail free card -- Shoe leather reporting -- Milestones -- Morning sickness -- Aftershocks -- Dershowitz v. Brown -- The feds -- The journalism resistance -- Katie Johnson -- Fireworks -- No apologies, no regrets -- Inmate 76319-054 -- Pedophile island -- Harvard, MIT, and the billionaires club -- In plain sight -- Jeffrey Epstein didn't kill himself -- The boss -- Conspiracies -- The reckoning -- Epilogue.
Includes bibliographical references (pages 437-446).
109039
Keywords: Epstein, Jeffrey, -- 1953-2019.; Human trafficking -- United States -- Case studies; Sex crimes -- United States -- Case studies; Criminal justice, Administration of -- Corrupt practices -- United States -- Case studies; Capitalists and financiers -- United States -- Case studies; Biography & Autobiography / Rich & Famous; Law / Criminal Law; True Crime; United States; Case studies